2022
DOI: 10.1590/0001-3765202220201718
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study about the impact of COVID-19 pandemic in a southern Brazilian state: the PAMPA cohort

Abstract: This study aimed to describe the effects of social distancing due to the COVID-19 pandemic on physical and mental health, chronic disease management, and economic situation in adults from a southern Brazilian state. Data from the baseline of the PAMPA (Prospective Study About Mental and Physical Health) cohort, a populationbased, longitudinal study is presented. An online-based questionnaire was used to assess the variables pre-and during social distancing. Most of the respondents (N=2,321)were women (76.7%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, SUS is the leading healthcare source for the low-income population [ 17 ]. Since most of our study sample is highly educated and consequently from mid- or high-income [ 10 ] and, in the private system, people are allowed to seek PT without a GP referral, this might explain the high proportion of participants who sought a PT before the pandemic. Also, although exercise interventions are one of the main strategies recommended to prevent and manage LBP, exercise professionals are usually not reported in the literature [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, SUS is the leading healthcare source for the low-income population [ 17 ]. Since most of our study sample is highly educated and consequently from mid- or high-income [ 10 ] and, in the private system, people are allowed to seek PT without a GP referral, this might explain the high proportion of participants who sought a PT before the pandemic. Also, although exercise interventions are one of the main strategies recommended to prevent and manage LBP, exercise professionals are usually not reported in the literature [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The institutional ethics board approved the study (protocol: 4.093.170). Details regarding the study design and methodology can be found elsewhere [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation